Formulation and characterization of ibuprofen sustained release tablets by solid dispersion technique - S.MANJU; Dr.C.RUBINA REICHAL (International Journal of Pharma and Bio Sciences, 2019)
The purpose of the investigation was to prepare sustained release tablets of ibuprofen by solid dispersion technique. The solubility of poorly soluble drug was enhanced by preparing solid dispersion of the drug with β-cyclodextrin in various concentrations (1:1,1:2,1:3). The optimized solid dispersions were kneaded with suitable proportions of rate controlling polymers such as HPMC K4M and HPMC K100M. The sustained release tablets were prepared by wet granulation method. The pre-compression parameters for blends and post-compression parameters for tablets were evaluated and all formulations showed desired pre and post compressed characteristics. The in vitro release studies were compared with that of innovator. The optimized formulations were fitted with various kinetic models and results revealed the diffusion release mechanism. Stability study was conducted as per ICH guidelines and the results showed that there is no physical or chemical change. It is concluded that an effective, rugged formulation technology is feasible with the advantages of sustained release action with minimum amount of dose for rheumatoid arthritis.